Earmarking policy: how it affects the Indonesian health and education sector - Fadli, Faishal; Sumantri, Vietha Devia Sagita (Intelektual Pustaka Media Utama, 2023)
This research analyses the implementation of earmarking policies in Indonesia that allocate 20% of expenditure for the education sector and 5% for the health sector by using the difference in difference method in the before and after the pandemic period. This research uses life expectancy at birth, number of maternal deaths, and the budget allocation for health as a representation of the health sector. To represent the education sector, this research uses primary education pupils, the primary school pupils-teacher ratio, and the budget allocation for education. This research also using propensity score matching and chow breakpoint test for robustness checks. The results of this research show the health and education sectors improved during the implementation of earmarking policy.